Exploitation of mineral resources and economic growth in CEMAC: The role of institutions - Armand Gilbert Noula; Salomon Leroy Ghamsi Deffo; Neville Zoatsa Mofow (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The objective of our study is to determine on one hand the effect of the exploitation of mineral resources on economic growth of CEMAC member countries, and on the other hand to examine the role of institutions in the transmission of these effects. Design/methodology/approach: To achieve our goals, we formulated an econometric model in panel data concerning countries of this economic community. Using the fixed effects method and two stage least squared method over the period 2002 to 2016, a period during which we observed not only a surge in the prices of natural resources in the markets but also a fall in the prices of basic resources following two large exogenous shocks. First, the "subprime" crisis and the 2015 oil crisis. Finding: From our findings, mineral rent has a positive and significant effects on economic growth. Subsequently, when we control our model with all the variables capturing institutions of governance (Voice and responsibility, Political stability and absence of violence / terrorism, Government Effectiveness - Regulatory quality, Rule of law, and Control of corruption), the results of our regressions were robust. In effect, good governance ensures the proper distribution of mineral rent throughout the economy and contributes to economic development. We came to the conclusion that these institutions of governance do not play a role in the transmission of the positive effects of mineral rent on economic growth. Research limitations/implications: The following where limitations encountered in our study. Firstly, the temporal dimension of our study (15 years). Secondly, the failure to take into account certain institutional variables such as democracy or the type of political regime. Originality/value: Our study enriches the literature of natural resource curse; it is in line with those who have shown that abundance in basic commodities or natural resource is not necessarily a hindrance to economic development.
Keywords: F21; F43; O33; 330; Growth; institutions; mineral resources